Analysis of the relationship between landslides and precipitation events in Chiriquí Province, Panama - Heinz, David (Universidad Tecnológica de Panamá, 2019)
Anthropogenic activity has long been labeled as the leading cause of soil destabilization. However, natural factors including soil erosion and excess rainfall have also been some of the main causes of landslides. Panama is a country with a tropical climate and has a variety of soils that are susceptible to weakening by rainfall. Some contain a considerable amount of clay (Acrisols, Nitisols) while others do not (Andosols). Either kinds of soil are structurally weakened by large amounts of rain. The landslides produced by the destabilization of these soils have caused much damage in Panama. Chiriqui is a province that has seen an increase in landslides. This study, using historical meteorological and disaster data from 1985 until 2010, was focused on determining the relationship between the amount of average rainfall and the frequency of landslides in Chiriqui. The study found that Bugaba experienced the highest number of landslides during the study period and received considerable rainfall.